Safety Culture of Physicians’ Medication in Saudi Arabia (Journal of Pharmaceutical Negative Results, 2022)
Objective: The study aims to demonstrate the Physicians’ Medication Safety Culture in Saudi Arabia.Methods: It examines a cross-sectional survey of physicians' medication safety practices in Saudi Arabia. It self-reported an electronic survey of physicians in Saudi Arabia, ranging from intern to consultant level, and physician specialties. The survey included respondents' demographic information about physicians who reported medication safety items in medical care, as well as medications who executed medication safety. With closed-ended questions, the 5-point Likert response scale system was used. The survey monkey system was used to analyze data on the Physicians’ Medication Safety Culture. In this study, the statistical package for social sciences (SPSS), Jeffery's Amazing Statistics Program (JASP), and Microsoft Excel sheet version 16 were used.Results: The total number of responding physicians was 253, with the majority 73 (54.07 %) coming from the central region, which was statistically significant among the areas (p<0.01). The majority of those who responded were from private hospitals 48(18.97%), MOH hospitals 41(16.21%), and University hospitals 40 (15.81%). Furthermore, 72 (60.50%) were female, while 47 (39.50%) were male, with a statistically significant difference (p<0.01). The average frequency of medications safety items reported monthly in medical care was (5.97), with the highest score element being Medication’s wastage services system (6.42), followed by Medications labelling before use (6.31), Medical drug information resources (6.15) and Medication’s safety committee for medical care (6.11). Anticoagulants 33 (33.33 %) and NSAIDs 32 (32.32 %) were the medications used in medication error reporting. Sedation medications 38(38.78%) and muscle relaxant medications 36 (36.73%) were the drugs used in ADR reporting. Antineoplastic 40 (40.00%) and Anti-seizure drug 39 (39.39%) were the most commonly used medicines in the looks like sound-alike system (38.24 %). Anti-arrhythmic 43 (43.88 %) and anti-psychotic medication 40 (40.40%) were the drugs used in the high alert medication system.Conclusion: The Physicians’ Medication Safety Cultures were inadequate and contradictory. Consequently, the physicians instituted non-serious aspects of medication safety culture. Hence, reviewing aspect medications safety cultures in medical practice with a focus on education and training is strongly advised in Saudi Arabia.